Description of Mixed-Phase Clouds in Weather Forecast and Climate Models - Tjernstroem, Michael (2014)
To develop improved parameterizations of so-called mixed-phase stratocumulus in numerical models of weather and climate, and of their impact on the surface energy budget over the Arctic Ocean, their impact on the vertical structure of the lower troposphere and relationships to larger-scale meteorology. Develop a process-level understanding addressing the processes responsible for making mixed-phase stratocumulus so common, by far the most common cloud type over the Arctic, when thermodynamic principles suggest that ice and liquid particles cannot coexist for extended periods of time. Find linkages between dynamic processes on all scales, ranging from long range transport to turbulent motions, and cloud micro-physics.